Automation Of Independent Path Searching using Depth First Search - Arwan, Achmad; Sagita, Denny (Journal of Information Technology and Computer Science, 2018)
In a basis path testing, there are independent paths that must be passed/tested at least once to make sure there are no errors in the code and ensure all pseudocode have implemented on the code. Previously, the independent path was generated using the Genetic Algorithm, but the number of iterations influenced the likelihood of the emergence of the corresponding the independent path. Besides, the pseudocode was also unable to be used directly since it must be implemented first, this makes finding an independent path longer because it has to implement the code. This research aims to find out how to find the independent path directly from pseudocode using a graph and how well the Depth First Search algorithm in finding the independent path. It was chosen because it was able to find the paths from a point to a particular point in a graph. The result of the system accuracy test was able to find the correct independent path as much as 52 from 76 test data, where the result of accuracy is 68.4% on average.